Sekolah Kebangsaan Puncak Alam 2 : adopt a student program / Nor Khaizan Anuar and Nadia Jalaludin - Anuar, Nor Khaizan; Jalaludin, Nadia (Faculty of Pharmacy, 2024)
On January 29, 2024, the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) demonstrated its commitment to community welfare with a heartening visit to Sekolah Kebangsaan Puncak Alam 2 (SKPA2) as part of their ongoing Adopt-a-Student initiative. This program, born in the wake of the COVID-19 pandemic in 2020, aims to provide financial support and educational enrichment to underprivileged students.